2007
DOI: 10.1002/ima.20114
|View full text |Cite
|
Sign up to set email alerts
|

Assessing human skin color from uncalibrated images

Abstract: Images of a scene captured with multiple cameras will have different color values because of variations in color rendering across devices. We present a method to accurately retrieve color information from uncalibrated images taken under uncontrolled lighting conditions with an unknown device and no access to raw data, but with a limited number of reference colors in the scene. The method is used to assess skin tones. A subject is imaged with a calibration target. The target is extracted and its color values ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 16 publications
0
29
0
6
Order By: Relevance
“…Our studies showed that our system gives a comparable distribution of predictions as that found between two cosmetic experts under different lighting conditions and different consumer imaging devices and different cosmetic product lines [9,10]. The system can be configured to plug in any expert opinion that the consumers like, or the brand wants, or the public respects, etc.…”
Section: Expert Ground Truthmentioning
confidence: 70%
See 1 more Smart Citation
“…Our studies showed that our system gives a comparable distribution of predictions as that found between two cosmetic experts under different lighting conditions and different consumer imaging devices and different cosmetic product lines [9,10]. The system can be configured to plug in any expert opinion that the consumers like, or the brand wants, or the public respects, etc.…”
Section: Expert Ground Truthmentioning
confidence: 70%
“…This matrix fixes the alteration of the image and maps it closer to the "true color". This means that pixels from the face can be relied on to accurately represent the subject's skin color [9,10].…”
Section: Imaging Pipelinementioning
confidence: 99%
“…A different method to assess skin tones and retrieve color information from uncalibrated images consists on imaging a skin region with a calibration target and extracting its color values to compute a color correction transform [52].…”
Section: Color Correctionmentioning
confidence: 99%
“…We have addressed these issues in great detail in [10,11], here we present a summary of the service's ability to color correct facial skin from un-calibrated images.…”
Section: Validation Of Color Correctionmentioning
confidence: 99%
“…We determined the correlation between imaged face color values and spectrally derived values to be high. The details of this analysis are published elsewhere [11].…”
Section: Imagers As Spectra-reading Substitutesmentioning
confidence: 99%